2019
DOI: 10.5546/aap.2019.eng.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological impact of varicella infection in children prior to the introduction of the varicella vaccine in the national immunization schedule of Argentina

Abstract: Introduction. In Argentina, an estimated 400 000 varicella cases occur annually. Given the under-recording of existing cases, the actual burden of disease is unknown. Objective. To assess the burden of varicella before the introduction of the varicella vaccine in the national immunization schedule. Materials and methods. Retrospective, analytical, observational study carried out in three hospitals of Argentina. Review of medical records from outpatient visits to the Emergency Department and from patients young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Of these, 52 studies were excluded from the meta-analysis, leaving 78 studies eligible for meta-analysis (Fig. 1 ) [ 6 9 , 28 , 30 – 32 , 34 , 35 , 37 , 38 , 41 , 43 , 46 , 47 , 51 , 53 , 57 68 , 71 74 , 76 78 , 81 , 85 , 87 , 91 94 , 99 102 , 104 , 105 , 107 , 109 , 112 114 , 116 118 , 120 , 121 , 124 , 125 , 128 132 , 134 , 136 , 138 140 , 142 , 143 , 145 147 , 150 ]. From the selected studies, 632 unique complications were extracted, of which 303 were included after clinical review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 52 studies were excluded from the meta-analysis, leaving 78 studies eligible for meta-analysis (Fig. 1 ) [ 6 9 , 28 , 30 – 32 , 34 , 35 , 37 , 38 , 41 , 43 , 46 , 47 , 51 , 53 , 57 68 , 71 74 , 76 78 , 81 , 85 , 87 , 91 94 , 99 102 , 104 , 105 , 107 , 109 , 112 114 , 116 118 , 120 , 121 , 124 , 125 , 128 132 , 134 , 136 , 138 140 , 142 , 143 , 145 147 , 150 ]. From the selected studies, 632 unique complications were extracted, of which 303 were included after clinical review.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has indicated that varicella complications occur mostly among immunocompromised patients [ 113 ], although recent studies have demonstrated that the burden of varicella complications is significant in patients without underlying disease [ 112 , 157 ]. The present study observed that immunocompetent patients when compared with immunocompromised patients had a significantly higher prevalence of neurological (11.73% vs 2.65%) and skin (27.49% vs 7.17%) complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, varicella-associated complications can occur in up to 12% of outpatients and 92.6% of inpatients [ 3 , 4 , 5 , 6 , 7 , 8 ]. Approximately 5% of patients with varicella who seek medical services will require hospitalization [ 9 ]. The most common complications are secondary bacterial infections of the skin and soft tissues, followed by pneumonia and encephalitis [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In countries with temperate climates such as Argentina, varicella is primarily a seasonal childhood disease with most cases occurring in late winter and spring (September to November) [ 9 , 10 , 11 ]. In regions with tropical and subtropical climates, varicella tends to be more pronounced in adolescents and adults [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…VZV infection is generally a mild illness consisting of moderate fever, mild cold symptoms, and a vesicular rash that develops scabs [1]. Some cases of varicella lead to serious complications such as encephalitis, pneumonia, and secondary bacterial infections; rarely, it results in death, especially for children younger than 1 year, immunocompromised patients, patients with impaired malignancies, and patients using immunosuppressive medications [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%